Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1002/anie.201201000
|View full text |Cite
|
Sign up to set email alerts
|

Unprecedented Reversible Redox Process in the ZnMFI—H2 System Involving Formation of Stable Atomic Zn0

Abstract: In its element: Zn(2+) at the M7 site of MFI-type zeolites activates H(2), via ZnH and OH species, and leads to Zn(0) species. The Zn(0) species returns to its original state, a Zn(2+) ion, upon evacuation of the zeolite at 873 K (see picture). The formation of the Zn(0) species is supported by DFT calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(98 citation statements)
references
References 49 publications
7
89
1
Order By: Relevance
“…[12][13][14] The final number shown in the sample notation indicates the ion exchange capacity that was evaluated by assuming one Zn 2+ -ion exchange per two protons in MFI.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14] The final number shown in the sample notation indicates the ion exchange capacity that was evaluated by assuming one Zn 2+ -ion exchange per two protons in MFI.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, our studies confirmed that this B3LYP-optimized MFI zeolite model comprised of 10-MR in cavities reproduced well the experimentally observed data. [12][13][14]22,[24][25][26][27][28][29][30][31] Taking our previous studies into consideration, we used the M7 site for the Al substitution position; 32 and we defined the Al configuration as the [M7-S2] arrangement. [12][13][14]30 To optimize fully the larger MFI geometry with a 10-MR cavity, we used the 6-311G(d) basis set for the zinc atom and the 6-31G (d) basis set for the Al atom, as well as four O atoms that were connected to the substituted Al atom.…”
Section: Computational Methodology (Calculation Method)mentioning
confidence: 99%
See 1 more Smart Citation
“…Oda et al. found that Zn 2+ ions in Zn‐ion‐exchanged MFI‐type zeolite were converted to stable Zn 0 species through a reaction with H 2 at 300 °C, and the atomic Zn 0 species could further react with AlOH to form paramagnetic Zn + species with the ultraviolet light excitation . Tamiyakul et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, ZnO crystals formed on Zn/H-ZSM5 prepared by impregnation were reduced to Zn 0 metal and eluted from the catalyst bed as a Zn vapor under typical propane aromatization conditions. Oda et al found that Zn 2 + ions in Zn-ion-exchanged MFI-type zeolite were converted to stable Zn 0 species through a reaction with H 2 at 300°C, [12] and the atomic Zn 0 species could further react with AlOH to form paramagnetic Zn + species with the ultraviolet light excitation. [13] Tamiyakul et al [14] showed that the ZnOH + species were converted to ZnH + by dehydroxylation after subjecting the Zn/H-ZSM5 to H 2 flow at 150°C.…”
Section: Introductionmentioning
confidence: 99%